2017
DOI: 10.48550/arxiv.1708.05288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a theory of unbounded locally solid Riesz spaces

Abstract: We introduce the notion of unbounded locally solid Riesz spaces, and investigate its fundamental properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In this case, we write x α un −→ x. A systematic study of unbounded convergences can be found in [5,7,9,15,16,18,24]. In general, unbounded order convergence is not topological.…”
Section: Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, we write x α un −→ x. A systematic study of unbounded convergences can be found in [5,7,9,15,16,18,24]. In general, unbounded order convergence is not topological.…”
Section: Preliminariesmentioning
confidence: 99%
“…A locally solid topology on a vector lattice X can be used to construct a new unbounded locally solid topology on X. We refer the reader to [4,6,7,9] for more details. Let X be a vector lattice.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations